Outcome of Endoscopic Third Ventriculostomy (ETV) in patients with Hydrocephalus of all age group-a single center study (Bangladesh Journal of Neurosurgery, 2026)
Endoscopic third ventriculostomy (ETV) is considered as a treatment of choice for obstructive hydrocephalus secondary  to congenital aqueduct stenosis. It can also be done in post infective, normal pressure hydrocephalus, hydrocephalus  secondary to posterior fossa tumor, myelomeningocele, and other causes. This study is done to evaluate the  outcome of ETV in patients with hydrocephalus of all age groups.  Methods:  This study was done in the Department of Neurosurgery, Rangpur Medical College Hospital from the period of June  2017 to October 2023. Within this period ETV was done in fifty-nine patients with hydrocephalus from different  etiologies in all age groups. Each case was properly evaluated by T2W axial and sagittal MRI of brain.  Results:  ETV was done in fifty-nine (59) patients with symptomatic HCP. Mean age was 15.38 ± 17.67 SD. Minimum age was  2 months and maximum 70 years. We did ETV below 6 months of age group in 5(8.5%) of cases. Between 6 months  to 10 years 26(44.1%) and between 11-20 years 13(22%) patients. ETV was done under 20 years in 44(74.6%)  patients, that represents maximum group of study population. In our study male was 26(44.1%) and female  33(55.9%) of patients. All patients were present with features of raised intracranial pressure.  Conclusion:  ETV is an effective treatment for selected patients with obstructive hydrocephalus. We can also do ETV in patients  with myelomeningocele, post-meningitis HCP with obstructive component NPH and other etiology. It needs long-term  follow-up to assess its failure rate.  Key words:  Endoscopic Third Ventriculostomy, Hydrocephalus, ventriculoperitoneal shunt. Bang. J Neurosurgery 2024; 14(1): 60-65